The August War in Georgia. - Oganjanyan, Amalia (Diplomica Verlag, 2012)
HauptbeschreibungReporting on a foreign war or a crisis is a challenging activity, a true professional test for a journalist. Media is often criticized for promoting violence by its conflict reporting: either by staying detached or by being biased. Peace, or conflict-sensitive, journalism was created for improvement of conflict coverage: it emphasizes the active role of journalists in de-escalation of conflict and encourages them to report on peaceful solutions. This relatively novel approach might be met with skepticism, as it appears too idealistic and demanding to be followed by journalists.